EFEKTIVITAS ANGGARAN KEUANGAN TAHUN 2010 s.d 2012 PADA KANTOR CAMAT TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Mardiana, Ida Iriyanti, Elfreda A Lau, (EKONOMIA, 2015)
Budgeting in government agencies necessary for the implementation of the basic tasks and functions that are entailed by the Office of Government can be done well, so that the function of public service to the people who need the service can be guaranteed well. Budget to support the implementation of activities office if effectively organized and planned course will provide the maximum benefit. Performance Based Budgeting means linking each funding as outlined in activities with expected outputs and outcomes, including effectiveness in achieving the results of the output. Outputs and results are set forth in the performance targets for each unit of word. Effectiveness is a measure of the results of a task or goal attainment. Effectiveness means meeting performance targets set. Head Office Tenggarong Seberang Kutai regency as one course required government agencies to devise and use the budget effectively obtained. Effectiveness in this case is the achievement of performance targets previously set as a benchmark the implementation of public service functions to the public performing well.Formulation of the problem of this research is